INFLUENCE OF INFORMATION COMMUNICATION TECHNOLOGY (ICT) INTEGRATION IN THE CURRICULUM AND TRAINER COMPETENCY SKILLS IN INFORMATION COMMUNICATION TECHNOLOGY (ICT) ON THE QUALITY OF EDUCATION IN VOCATIONAL TRAINING CENTERS: A CASE STUDY OF MURANG'A COUNTY - Wakasiakah, Pauline Nelima; Mwalili, Dr. Tobias; Senaji, Dr. Thomas (African Journal of Education and Practice, 2018)
Purpose: The purpose of this paper is to assess the influence of Integrating ICTs in the curriculum and the trainer competency skills in ICT have on the quality of training in Vocational Training Centers (VTCs) in Murang'a County, Kenya. Methodology: The study used a descriptive research design to establish the relationship between ICT integration in the curriculum, Trainer competency skills in ICTs and the quality of education in VTCs. The population was sixty three (63), which was a census of all the VTCs in Murang'a. A questionnaire was administered at the end of the training to capture the pre and post training experience and test the effectiveness of the training. The analysis of the data was conducted through descriptive and inferential statistics. Results: The findings indicated that VTC trainers lacked ICT skills this was based on them not being proficient in performing basic tasks asked by the researcher and on the integration of ICTs in the curriculum the findings indicated that, VTCs were not using ICTs to deliver the curriculum. Trainers indicated that they used ICTs only for record keeping but not as a tool for training or further research or even for demonstration videos available online. Unique contribution to theory, practice and policy: It was recommended that Murang'a County should come up with a policy which ensures that all the trainers in the VTCs have proper ICT skills if possible take them for courses on ICTs and how they can be used in their various trades/courses. As for ICTs integration in the curriculum, it was recommended that, the County should partner with Kenya Institute of Curriculum Development ( KICD) and other stakeholders, to come up with a curriculum that is inclusive of ICT. The County should also come up with demonstration CDs, DVDs and audio tapes to enable learning or training even when the trainer is absent.